Investigating the influence of gender and boy-mass index on thermal sensation / Siti Nur Imani Mustaffa, Fairus Muhamad Darus and Rabiatul Adawiyah Nasir - Mustaffa, Siti Nur Imani; Muhamad Darus, airus; Nasir, Rabiatul Adawiyah (College of Built Environment, 2023)
Thermal comfort is an essential aspect of human well-being and can be defined as a state of satisfaction with the thermal environment.